Letting Them In: Sharing Your Story with People outside of Your Industry - Brandon Telg; Jaron Jones; Ricky Telg (EDIS)
Those who work in agriculture often face the challenge of explaining their work to people outside of their field. Identifying what your audience cares about is the first step in formulating a story your audience will understand and value. This 3-page fact sheet also offers do’s and don’ts for crafting a story for non-expert audiences. Written by Brandon Telg, Jaron Jones, and Ricky Telg, and published by the UF Department of Agricultural Education and Communication, July 2015. (Photo credit: monkeybusinessimages/iStock/Thinkstock.com)